Broadband Wide‐Angle Multifunctional Polarization Converter via Liquid‐Metal‐Based Metasurface. Issue 7 (8th February 2017) - Wu, Pin Chieh; Zhu, Weiming; Shen, Zhong Xiang; Chong, Peter Han Joo; Ser, Wee; Tsai, Din Ping; Liu, Ai‐Qun
Abstract : Metasurfaces enable flat optical components with predesigned functionalities, including the polarization conversion using subwavelength elements. However, switching between different functionalities of the metasurface‐based optical components is extremely difficult because subwavelength elements have to be finely addressed to change the spatial phase gradient for desired functionality. Here, it is demonstrated, for the first time, a broadband wide‐angle multifunctional polarization converter via galinstan‐based metasurface with each element array actively addressed. The switching between different functionalities is realized by controlling L‐shaped galinstan resonator using microfluidic channels, which maintain the optical performances, that is, broadband and large angular tolerance, of the polarization converter. Furthermore, the galinstan‐based metasurface is also demonstrated to function as a broadband optical attenuator, which provides prospects for various applications, such as smart radar, stealth technology, and light manipulation for quantum communication. Abstract : A liquid‐metal‐based metasurface is demonstrated for broadband wide‐angle multifunctional polarization conversion in different polarization states: linear, circular, and elliptical, by dynamically reconfiguring through the tuning of the L‐shaped resonators. The bandwidth is >60% and the angular tolerance is 45°. This is a significant milestone for metasurface applications such as smart radar and light manipulation for quantum computing and communication, etc.